Building the Essence of A Nation With Diverse Cultures Through Multicultural Education - Rio Era Deka (Jurnal Ijtihad, 2023)
Cultural diversity (multicultural) is a natural event due to the meeting of various cultures, the interaction of various individuals and groups by bringing cultural behavior, having different and specific ways of life. Diversity such as cultural diversity, family background, religion, and ethnicity interact with each other in the Indonesian community. The intensity of interaction between humans is quite high, so that the social skills of citizens in interacting with each other need to be possessed by every member of society. Multicultural education teaches the meaning of love for the homeland, nationalism, or values of commitment about how to become a strong citizen physically and mentally, and have special integrity, so this can be categorized as a form of effort that is appreciated by Islamic teachings, because it is oriented towards character and nation building.